ACP-EU Update: EU Task Force on Land Tenure - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Most international institutions and donor agencies now recognize that land issues, in particular well organized land tenure systems, are crucially important for economic development and growth, poverty reduction and governance in the developing world.